Improving Arabic language speaking skill of non-Arabic students in Karabuk University - Riza Ashari; Jaziela Huwaida; Flora Nikaso; Rihan Nurul Aini (Universitas Muhammadiyah Malang, 2024)
The lack of understanding of Arabic among non-Arabic students at the Faculty of Divinity at Karabuk University is one of the factors that hinder them from understanding lessons, especially in courses such as qira'ah, tafsir, hadith, and others. This lack of language mastery causes difficulties in comprehending materials that requires a deep understanding of Arabic texts. Thus, this project aims to conducting several activities to improve and broaden the knowledge of students at Karabuk university. The subjects of this activity were 40 students from Karabuk University. The methods used implemented were direct methods and question and answer methods, through several stages of implementation, namely preparation, implementation, and monitoring and evaluation. The results of the implementation of this activity show that the students managed to gain a deeper understanding of the Arabic language learning methods applied in Gontor. This insight is not only limited to theory, but also involves direct practice as shown through the active interaction between Santri and Turkish presenters during the teaching process. This interaction is an important element, as it allows santri to experience teaching approaches from different perspectives and interact with international teachers, which enriches their learning experience. Thus, this activity not only increases the santri’s knowledge of teaching methods, but also builds cross-cultural communication abilities and strengthens their Arabic language skills through hands-on practice and guidance from experienced presenters.